2001
DOI: 10.1038/sj.bjp.0704340
|View full text |Cite
|
Sign up to set email alerts
|

Anandamide‐induced relaxation of sheep coronary arteries: the role of the vascular endothelium, arachidonic acid metabolites and potassium channels

Abstract: 1 The e ects of the endocannabinoid, anandamide, and its metabolically stable analogue, methanandamide, on induced tone were examined in sheep coronary artery rings in vitro. 2 In endothelium-intact rings precontracted to the thromboxane A 2 mimetic, U46619, anandamide (0.01 ± 30 mM) induced slowly developing concentration-dependent relaxations (pEC 50 [negative log of EC 50 ]=6.1+0.1; R max [maximum response]=81+4%). Endothelium denudation caused a 10 fold rightward shift of the anandamide concentration-relax… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
55
0
2

Year Published

2003
2003
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(58 citation statements)
references
References 35 publications
(118 reference statements)
1
55
0
2
Order By: Relevance
“…In respect of the latter, it has been shown that sensory nerves do not play a role in coronary vessels from several species (Grainger & Boachie-Ansah, 2001;White et al, 2001;Ford et al, 2002). This indicates that the actions of anandamide may be dependent on vanilloid receptor density and/or density of perivascular nerve in a given blood vessel.…”
Section: Introductionmentioning
confidence: 94%
See 2 more Smart Citations
“…In respect of the latter, it has been shown that sensory nerves do not play a role in coronary vessels from several species (Grainger & Boachie-Ansah, 2001;White et al, 2001;Ford et al, 2002). This indicates that the actions of anandamide may be dependent on vanilloid receptor density and/or density of perivascular nerve in a given blood vessel.…”
Section: Introductionmentioning
confidence: 94%
“…In the rat aorta, anandamide causes approximately a 20% maximal relaxation (O'Sullivan et al, 2004a), while in the rabbit aorta, this has been reported to be 80% (Mukhopadhyay et al, 2002). Similarly, in the rat coronary vessels anandamide causes about 30-40% relaxation (White et al, 2001), 50% relaxation in bovine vessels (Pratt et al, 1998) but 80% relaxation in ovine vessels (Grainger & Boachie-Ansah, 2001). However, anandamide does not cause vasorelaxation in porcine coronary vessels (Fleming et al, 1999).…”
Section: Species Differences the Vascular Responsiveness Towardsmentioning
confidence: 99%
See 1 more Smart Citation
“…Herein, we demonstrate that AEA mediates hypoxic pulmonary vasoconstriction and is also involved in pulmonary hypertension via its degradation to FAAH-dependent metabolites. Effects of endocannabinoids on vascular tone have been mainly attributed to direct endocannabinoid signaling via surface receptors (1, 2, 21) so far, whereas degradation pathways of endocannabinoids have been thought to play a minor role (4,22). FAAH is the principal AEAdegrading enzyme, thereby limiting the effects of AEA at cannabinoid receptors.…”
Section: Discussionmentioning
confidence: 99%
“…In the porcine coronary artery, vasodilators such as bradykinin stimulate production of reactive oxygen species by cytochrome P450 enzymes in the endothelium (Fleming et al, 2001) and trigger a series of events that results in activation of large-conductance Ca 2ϩ -dependent K ϩ currents and vasodilation (Barlow and White, 1998;Hayabuchi et al, 1998b;Pomposiello et al, 1999). One of these events appears to include release of a cyclooxygenase-independent metabolite of arachidonic acid Cohen, 1991, 1992;Hecker et al, 1994;Weintraub et al, 1995;Chataigneau et al, 1998;Hayabuchi et al, 1998a), one which is not a cannabinoid (Chataigneau et al, 1998;Pomposiello et al, 1999;Grainger and Boachie-Ansah, 2001). Although many acknowledge that cytochrome P450 plays a key role in the production of EDHF(s) in this tissue Fleming et al, 2001;Busse et al, 2002), it is not clear whether the vasoactive metabolite is an epoxyeicosatrienoic acid or some oxygen free radical, which could, in turn, lead to generation of isoprostanes.…”
mentioning
confidence: 99%